2019
DOI: 10.1136/rapm-2019-100418
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic blocks for complex regional pain syndrome: a survey of pain physicians

Abstract: BackgroundSympathetic blocks (SB) are commonly used to treat pain from complex regional pain syndrome (CRPS). However, there are currently no guidelines to assist pain physicians in determining the best practices when using and performing these procedures.MethodsA 32-question survey was developed on how SBs are used and performed to treat CRPS. The survey was conducted online via SurveyMonkey. The responses were statistically analyzed using descriptive statistics, and comparing academic versus non-academic, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 28 publications
(17 reference statements)
0
23
0
Order By: Relevance
“…146 However, the only RCT comparing triamcinolone and bupivacaine with only bupivacaine for celiac plexus block (chronic pancreatitis) found no differences in the success rate. 147 We found it surprising that there was not a single RCT evaluating the role of steroids in sympathetic blocks, given that nearly 50% pain physicians add them, 148 including near highly vascular structures. 149 Other common conditions in which steroid injections are considered include epicondylitis, and bursa injections, which we considered under soft tissue structures.…”
Section: Discussionmentioning
confidence: 99%
“…146 However, the only RCT comparing triamcinolone and bupivacaine with only bupivacaine for celiac plexus block (chronic pancreatitis) found no differences in the success rate. 147 We found it surprising that there was not a single RCT evaluating the role of steroids in sympathetic blocks, given that nearly 50% pain physicians add them, 148 including near highly vascular structures. 149 Other common conditions in which steroid injections are considered include epicondylitis, and bursa injections, which we considered under soft tissue structures.…”
Section: Discussionmentioning
confidence: 99%
“…Holistic care for patients involves treating musculoskeletal pain in the context of the Cervical and lumbar epidural steroid injections shown effective for short-term radicular pain symptoms [118,119] Fair evidence for chronic thoracic pain and limited for post thoracotomy pain [120] Failure, pain, IV injection, intrathecal injection, headache, hypotension, infection (rare), epidural hematoma (rare), vascular spasm or injury with transforaminal approach Percutaneous adhesiolysis [121,122] Lumbar post-surgery syndrome (FBSS)…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence for effectiveness in the treatmentof chronic refractory low back and lower extremity pain [122] Failure, pain, IV injection, intrathecal injection, headache patient's life such that comorbid conditions, lifestyle, patient preferences, and mental health are all taken into account. Conservative therapies such as weight loss, healthful eating, exercise, and relaxation techniques can be helpful along with assistive devices (such as braces or shoe orthotic inserts) along with psychological counseling and coping skills, but these approaches require a level of motivation and commitment on the part of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…A stellate ganglion block is the most commonly used simple technique to interrupt the sympathetic innervation of the upper extremity [ 8 ]. However, clinical and anatomical studies have suggested that this may not be the best method for upper extremity sympathetic block [ 7 , 9 , 18 ].…”
Section: Discussionmentioning
confidence: 99%